Preliminary Study of the Mechanical Propertres of Impregnated Fibers with Nanoencapsulated Repellents for Aedes Aegypti - Zárate, Juan Camilo
The development of insect-repellent products has been widely used with the aim of reducing and giving protection from viruses like Zika, Chikungunya and Dengue; diseases particularly related to the species Aedes aegypti. One of the main issues has been the biocompatibility of these synthetic compounds due to their generation of adverse reactions on people. Nanoencapsulated, developed using natural extracts, are to be impregnated on textiles in order to achieve a repellent effect in different fibers and dressmaking fabrics. In this preliminary study, four textile fabrics were independently evaluated among which are natural-synthetic fibers, polyester fibers and cotton fibers. Mechanical evaluations were designed for the impregnated fibers, according to their compositions, in order to determine the appropriate values of mechanical effort.